Intestinal sodium/glucose cotransporter 3 expression is epithelial and downregulated in obesity - Soták, Matúš; Casselbrant, Anna; Rath, Eva; Zietek, Tamara; Strömstedt, Maria; Adingupu, Damilola D; Karlsson, Daniel; Fritsch Fredin, Maria; Ergang, Peter; Pácha, Jiří; Batorsky, Anna; Alpers, Charles E; et al. (Life sciences, 2021)
AIM: We aimed to determine whether the sodium/glucose cotransporter family member SGLT3, a proposed glucose sensor, is expressed in the intestine and/or kidney, and if its expression is altered in mouse models of obesity and in humans before and after weight-loss surgery. MAIN METHODS: We used in-situ hybridization and quantitative PCR to determine whether the Sglt3 isoforms 3a and 3b were expressed in the intestine and kidney of C57, leptin-deficient ob/ob, and diabetic BTBR ob/ob mice. Western blotting and immunohistochemistry were also used to assess SGLT3 protein levels in jejunal biopsies from obese patients before and after weight-loss Roux-en-Y gastric bypass surgery (RYGB), and in lean healthy controls. KEY FINDINGS: Sglt3a/3b mRNA was detected in the small intestine (duodenum, jejunum and ileum), but not in the large intestine or kidneys of mice. Both isoforms were detected in epithelial cells (confirmed using intestinal organoids). Expression of Sglt3a/3b mRNA in duodenum and jejunum was significantly lower in ob/ob and BTBR ob/ob mice than in normal-weight littermates. Jejunal SGLT3 protein levels in aged obese patients before RYGB were lower than in lean individuals, but substantially upregulated 6 months post-RYGB. SIGNIFICANCE: Our study shows that Sglt3a/3b is expressed primarily in epithelial cells of the small intestine in mice. Furthermore, we observed an association between intestinal mRNA Sglt3a/3b expression and obesity in mice, and between jejunal SGLT3 protein levels and obesity in humans. Further studies are required to determine the possible role of SGLT3 in obesity.
Keywords: obezita; Gastric Bypass; exprese genu; SLC5A4; hmotnostní úbytek; Humans; messenger RNA; Gene Expression; lidé středního věku; Insulin Resistance; Down-Regulation; T2M; Roux-en-Y gastric bypass; jejunum; High-fat diet; Female; střevní sliznice; dospělí; tenké střevo; lidé; Jejunum; zvířata; myši; žaludeční bypass; transportní proteiny pro sodík a glukosu; myši inbrední C57BL; down regulace; Mice; protein - isoformy; Adult; Protein Isoforms; RNA, Messenger; Intestine, Small; ženské pohlaví; Male; Leptin; Middle Aged; inzulinová rezistence; Insulin; leptin; Mice, Inbred C57BL; transkriptom; Transcriptome; Obesity; Leptin deficiency; Animals; mužské pohlaví; Disease Models, Animal; Intestinal Mucosa; Sodium-Glucose Transport Proteins; Weight Loss; inzulin; modely nemocí na zvířatech